Drilling of a hybrid Al/SiC/Gr metal matrix composites - AY, MUSTAFA (SPRINGER LONDON LTD, 2012)
The present study investigates the influence of cutting parameters on cutting force and surface roughness in drilling of Al/20%SiC/5%Gr and Al/20%SiC/10%Gr hybrid composites fabricated by vortex method. The drilling tests are conducted with diamond-like carbon-coated cutting tools. This paper is an attempt to understand the machining characteristics of the new hybrid metal matrix composites. The results indicate that inclusion of graphite as an additional reinforcement in Al/SiCp reinforced composite reduces the cutting force. The cutting speed and its interactions with feed rate are minimum. Feed rate is the main factor influencing the cutting force in both composites. The surface roughness value is proportional with the increase in feed rate while inversely proportional with cutting speed in both composites. For all cutting conditions, Al/20%SiC/10%Gr composite has lower surface roughness values than Al/20%SiC/5%Gr composite. The surface is analyzed using scanning electron microscope.
Keywords: Hybrid MMCs; Machinability; Graphite; Cutting forces; PART II; MACHINABILITY; DIAMOND